2021
DOI: 10.3390/sym13050735
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a Good Indicator for Estimated Prime Factor and Its Modification in Fermat’s Factoring Algorithm

Abstract: Fermat’s Factoring Algorithm (FFA) is an integer factorisation methods factoring the modulus N using exhaustive search. The appearance of the Estimated Prime Factor (EPF) method reduces the cost of FFA’s loop count. However, the EPF does not work for balanced primes. This paper proposed the modified Fermat’s Factoring Algorithm 1-Estimated Prime Factor (mFFA1-EPF) that improves the EPF method. The algorithm works for factoring a modulus with unbalanced and balanced primes, respectively. The main results of mFF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The various sizes of n included in this experiment are 64 bits, 128 bits, 256 bits 512 bits, 1024 bits, and 2048 bits. However, all prime factors of p − 1 or q − 1 are the members of B = {2, 3,5,7,11,13,17,19,23,29,31,37,41,43,47,53,59, 61, 67, 71, 73, 79, 83, 89, 97}, a prime number which is between 1 and 100. In addition, IPP1_V2 is compared to Pollard's p − 1 [26] and Pollard's p − 1 [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The various sizes of n included in this experiment are 64 bits, 128 bits, 256 bits 512 bits, 1024 bits, and 2048 bits. However, all prime factors of p − 1 or q − 1 are the members of B = {2, 3,5,7,11,13,17,19,23,29,31,37,41,43,47,53,59, 61, 67, 71, 73, 79, 83, 89, 97}, a prime number which is between 1 and 100. In addition, IPP1_V2 is compared to Pollard's p − 1 [26] and Pollard's p − 1 [28].…”
Section: Resultsmentioning
confidence: 99%
“…However, this method, which is called the estimated prime factor (EPF) [10], cannot be chosen to solve n derived from the balanced primes. In 2021, EPF was improved [11] to solve n which is generated from unbalanced primes or balanced primes. Therefore, the modified method can be chosen to recover p and q without the mistake.…”
mentioning
confidence: 99%
“…In addition, a technique known as an estimated prime factor (EPF) was improved by Tahir et. al [7] to solve N generated from balanced or unbalanced primes p and q. Furthermore, Pollard [8] showed that N with a small size is easily factored since the complexity of the factorization algorithm depends on the size of √ N. Subsequently, research undertaken by many others [9][10][11] extended this complexity using the number field sieve method, which has dominated efforts to factor the RSA modulus ever since.…”
Section: Introductionmentioning
confidence: 99%
“…Many problems in number theory and computer arithmetic play important roles in cryptography. Examples of such problems are the generation of prime numbers [1][2][3], primality testing [4,5], modular exponentiation [6], addition chains and sequences [7,8] and integer factorization [9][10][11][12]. Developing fast algorithms that address these problems is one of the main challenges of algorithm complexity and leads to significant improvements in various applications.…”
Section: Introductionmentioning
confidence: 99%